2022
DOI: 10.1186/s13045-022-01294-4
|View full text |Cite
|
Sign up to set email alerts
|

Exploring immunotherapy in colorectal cancer

Abstract: Chemotherapy combined with or without targeted therapy is the fundamental treatment for metastatic colorectal cancer (mCRC). Due to the adverse effects of chemotherapeutic drugs and the biological characteristics of the tumor cells, it is difficult to make breakthroughs in traditional strategies. The immune checkpoint blockades (ICB) therapy has made significant progress in the treatment of advanced malignant tumors, and patients who benefit from this therapy may obtain a long-lasting response. Unfortunately, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
104
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(105 citation statements)
references
References 223 publications
(208 reference statements)
0
104
0
1
Order By: Relevance
“…Furthermore, recent research has also described a significant interaction between the PD-1/PD-L1 axis and the EGFR pathway [ 28 ]. These mechanisms ultimately help the tumor to escape anti-tumor immunity [ 3 , 4 , 5 , 28 , 29 , 30 , 31 ]. Therefore, monoclonal antibodies have been developed to antagonize this inhibitory signaling, and in the last decade, several randomized clinical trials have investigated the efficacy and safety of immune checkpoint inhibitors, including anti-PD-1 and anti-PD-L1 drugs [ 29 , 30 , 31 , 32 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, recent research has also described a significant interaction between the PD-1/PD-L1 axis and the EGFR pathway [ 28 ]. These mechanisms ultimately help the tumor to escape anti-tumor immunity [ 3 , 4 , 5 , 28 , 29 , 30 , 31 ]. Therefore, monoclonal antibodies have been developed to antagonize this inhibitory signaling, and in the last decade, several randomized clinical trials have investigated the efficacy and safety of immune checkpoint inhibitors, including anti-PD-1 and anti-PD-L1 drugs [ 29 , 30 , 31 , 32 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…These mechanisms ultimately help the tumor to escape anti-tumor immunity [ 3 , 4 , 5 , 28 , 29 , 30 , 31 ]. Therefore, monoclonal antibodies have been developed to antagonize this inhibitory signaling, and in the last decade, several randomized clinical trials have investigated the efficacy and safety of immune checkpoint inhibitors, including anti-PD-1 and anti-PD-L1 drugs [ 29 , 30 , 31 , 32 , 33 , 34 ]. The most immunological response is expected in those (metastatic) CRC patients who have tumors with deficient mismatch-repair and/or high levels of microsatellite instability [ 29 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the percentage of patients eligible for ICI therapy has increased from 1.54% in 2011 to 43.63% in 2018 ( 4 ), the portion of patients that benefits from these therapies remains limited ( 8 11 ). For example, in metastatic colorectal cancer (mCRC) in which the 5-year survival is 15%, only 3.5%-6.5% of mCRC patients respond to ICB ( 9 – 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although the percentage of patients eligible for ICI therapy has increased from 1.54% in 2011 to 43.63% in 2018 ( 4 ), the portion of patients that benefits from these therapies remains limited ( 8 11 ). For example, in metastatic colorectal cancer (mCRC) in which the 5-year survival is 15%, only 3.5%-6.5% of mCRC patients respond to ICB ( 9 – 11 ). In advanced cancers, such as head and neck squamous cell carcinoma (HNSCC) and advanced melanoma, only 15%-20% and 33%-44% of the patients, respectively, benefit with pembrolizumab or nivolumab (anti-PD-1) treatment ( 4 , 8 , 12 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that high mutational burden and PD-L1 expression of urothelial carcinoma made it more sensitive to immunotherapy (2,3), and several ICs had been approved to treat it (4). Similarly, ICIs had also shown good clinical efficacy in prostatic cancer (5), penile cancer (6), testicular cancer (7), colorectal cancer (8), and esophagus cancer (9). Additionally, nivolumab, pembrolizumab, camrelizumab, and tislelizumab had been approved to treat Hodgkin lymphoma (HL) (10).…”
Section: Introductionmentioning
confidence: 99%